Professoras de Educação Infantil em época de COVID-19: relato de experiência sobre as atividades - Oshiro , Andreia Mayumi (2021)
The COVID-19 pandemic caused by coronavirus has affected several sectors, including the educational one. In this context, Education Departments have restructured their schools and implemented actions aiming at preventing the spread of contagious. One of these actions was the replacement of face-to-face teaching by remote teaching. Accordingly, this article aims to share experiences of early education teachers on activities that have been developed in this phase of the Basic Education. The teachers involved in the present study work at a Public Center for Early Childhood Education located in a city of São Paulo State. The experience report method was used.